Pengembangan Standar Penilaian Dalam Pembelajaran P endidikan A gama I slam - Mahrus (Jurnal Pendidikan Islam, 2019)
Abstract: assessment of learning outcomes is referred to individual assessment which emphasizes more on cognitive aspects. So in this framework assessment must provide the same portion in each do main, both cognitive, affective and psychomotor. Moreover, religious education subjects do not just understand the material to students, but also must be able to be applied in everyday life behavior.